Injury incidence, severity and type across the menstrual cycle in female footballers: a prospective three season cohort study - Barlow, A.; Blodgett, J. M.; Williams, S.; Pedlar, C. R.; Bruinvels, G. (Medicine & Science in Sports & Exercise, 2024)
Purpose The aim of the study was to assess the influence of menstrual cycle phase on injury incidence, severity and type in elite female professional footballers over three seasons.